Clinical evaluation protocol for chronic rhinosinusitis with polyposis during treatment with biological agents - Pedro Marques Gomes; Diogo Cunha Cabral; André Carção; Joana Barreto; Ana Isabel Gonçalves; Paula Azevedo; José Penêda; Delfim Duarte; Miguel Viana (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Chronic rhinosinusitis with nasal polyposis is a common pathology in Otorhinolaryngology, and the therapeutic options, in a simplified way, are medical and/or surgical. Medical therapeutic options, in addition to topical and oral corticosteroid therapy, include the use of biological agents. Three biological agents were recently approved for the treatment of chronic rhinosinusitis with nasal polyposis in Portugal, being indicated in critically ill patients not controlled with topical nasal corticosteroid therapy, for whom surgery (unless contraindicated) and/or systemic corticosteroid therapy did not provide adequate control of the disease.